2009
DOI: 10.1167/iovs.08-2133
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Retinal Gliosis in Transgenic Mice Induced by Kainic Acid Neurotoxicity

Abstract: The current real-time fluorescent imaging method described here is a powerful preclinical tool to directly monitor retinal gliosis caused by various retinopathies. In addition, this molecular imaging method should be useful in assessing retinal neurotoxicity and in therapeutic development in a preclinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Since then, transgenic models have been engineered in which astrocytes express GFP (Zhuo et al, 1997; Nolte et al, 2001), allowing for the observation of astrogliosis in brain slices with fluorescent microscopy, and real-time in vivo detection of astrogliosis using multi-photon microscopy. This technique has been employed by several groups investigating systems such as retinal gliosis in diabetes (Kumar and Zhuo, 2010), retinal neurotoxicity (Ho et al, 2009) and NMDA-induced astrocyte activation (Serrano et al, 2008). This transgenic model can also facilitate sorting of astrocytes from surrounding brain tissue, allowing mRNA expression profiling in glioma (Katz et al, 2012), as described above.…”
Section: Imaging Astrocytes In Vivomentioning
confidence: 99%
“…Since then, transgenic models have been engineered in which astrocytes express GFP (Zhuo et al, 1997; Nolte et al, 2001), allowing for the observation of astrogliosis in brain slices with fluorescent microscopy, and real-time in vivo detection of astrogliosis using multi-photon microscopy. This technique has been employed by several groups investigating systems such as retinal gliosis in diabetes (Kumar and Zhuo, 2010), retinal neurotoxicity (Ho et al, 2009) and NMDA-induced astrocyte activation (Serrano et al, 2008). This transgenic model can also facilitate sorting of astrocytes from surrounding brain tissue, allowing mRNA expression profiling in glioma (Katz et al, 2012), as described above.…”
Section: Imaging Astrocytes In Vivomentioning
confidence: 99%
“…(Bosco et al, 2015) Ho et al, have also used in vivo longitudinal CSLO imaging to document gliotic responses of astrocytes within the ONH after RGC injury. (Ho et al, 2009)…”
Section: Introductionmentioning
confidence: 99%
“…In search for an alternative noninvasive imaging method to investigate the ocular consequence in Parkinsonism or other neurological disorders, we developed a molecular retinal imaging system, comprising of a GFAP‐GFP mouse [16], a confocal scanning laser ophthalmoscope, and an image processing algorithm [14,15]. Results from the current study showed that this imaging system can be applied to study retinopathy in a neurotoxicant (2′‐CH 3 ‐MPTP)‐induced mouse PD model.…”
Section: Discussionmentioning
confidence: 99%
“…For imaging hardware, the second version of Heidelberg Retina Angiograph (HRA II) SLO (Heidelberg Engineering, Dossenheim, Germany) was modified for use on mice. Detailed procedures for imaging and signal quantification were described in our recent publication [14]. The quantified signal values were expressed as mean ± SEM, and statistically tested using Student's two‐tailed t ‐test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation